(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2020)
The Palembang city still has several locations for Final Disposal Sites, one of which is located in Sukarame District. Sukawinatan landfill began operations in 1994 with a land area of 25 hectares and has been used 15 hectares, the remaining 10 hectares of land is estimated to be able to accommodate waste until 2028. In some part, groundwater is still used for daily life originating from groundwater, especially in RT 68, which is used for domestic needs such as bathing, brushing teeth, washing clothes, washing utensils, and cooking. The results showed that based on the physical parameters it was concluded that 5 odor samples fulfilled the requirements, 5 taste samples fulfilled the requirements, 4 samples of dissolved solids met the requirements, 3 turbidity samples fulfilled the requirements, and 5 temperature and color samples met the requirements. Based on the chemical parameters it was concluded that the five samples did not exceed the maximum permissible levels except for pH parameters. Based on organic chemical parameters it is concluded that all samples meet the criteria of organic chemistry. The water quality index of all good samples is very good.